2010
DOI: 10.1007/s10103-010-0852-3
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Candida albicans, Staphylococcus aureus, and Streptococcus mutans biofilms to photodynamic inactivation: an in vitro study

Abstract: The purpose of this study was to evaluate specific effects of photodynamic inactivation (PDI) using methylene blue as photosensitizer and low-power laser irradiation on the viability of single-, dual-, and three-species biofilms formed by C. albicans, S. aureus, and S. mutans. Biofilms were grown in acrylic discs immersed in sterile brain heart infusion broth (BHI) containing 5% sucrose, inoculated with microbial suspension (10(6) cells/ml) and incubated for 5 days. On the fifth day, the effects of the methyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
123
0
21

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(152 citation statements)
references
References 30 publications
8
123
0
21
Order By: Relevance
“…Therefore, according to this study parameters and the cost-benefit ratio regarding the drug concentration and the clinical procedure time, the PDT protocol proved effective when used the 5-minutes incubation and the methylene blue concentration of 150 µg/mL. Using the 5-minutes incubation and methylene blue concentrations of 100μg/mL, 150μg/mL and 50 μg/ mL, Pereira et al 7 , Queiroga et al 9 and Giroldo et al 22 , respectively, observed a significant reduction in cell viability of Candida albicans species.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Therefore, according to this study parameters and the cost-benefit ratio regarding the drug concentration and the clinical procedure time, the PDT protocol proved effective when used the 5-minutes incubation and the methylene blue concentration of 150 µg/mL. Using the 5-minutes incubation and methylene blue concentrations of 100μg/mL, 150μg/mL and 50 μg/ mL, Pereira et al 7 , Queiroga et al 9 and Giroldo et al 22 , respectively, observed a significant reduction in cell viability of Candida albicans species.…”
Section: Discussionmentioning
confidence: 79%
“…The studies of Dai et al 1 , Kato et al 4 , Teichert et al 6 , Pereira et al 7 , Souza et al 8 , Queiroga et al 9 , Munin et al 10 , Silva Martins et al 17 , Giroldo et al 22 and Souza et al 23 , investigated the effects of photodynamic therapy on the viability of Candida albicans using methylene blue as a photosensitizer. The results of these studies proved the antifungal effect of this treatment modality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it possible to suggest that CUR-mediated PDT can act against Candida biofilms in a similar way, simultaneously altering yeast metabolism and causing biofilm disarticulation. It has been suggested that lethal photosensitization is likely to occur in the outermost layers of C. albicans biofilms probably due to the superficial penetration of PS into the biofilm layers [43]. Since PDT can superficially disrupt the biofilm structure after a single application, it is possible to suppose that repeated cycles of the therapy may be capable of reducing the biofilm biomass, allowing deeper penetration of the PS and promoting higher levels of biofilm inactivation.…”
Section: Discussionmentioning
confidence: 99%